2014
DOI: 10.1210/jc.2014-1001
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab for Treatment of Hypercalcemia of Malignancy

Abstract: Introduction: Hypercalcemia is a common metabolic disorder in patients with malignant diseases; it is primarily associated with multiple myeloma and other hematological malignancy, but hypercalcemia is also found in advanced solid cancers, particularly squamous cell cancer as lung cancer, head and neck cancer, breast cancer, kidney and prostate cancer [1]. Frequent clinical manifestations of malignancy-related hypercalcemia are: nausea, vomiting, ileus, anorexia, dehydration, renal failure, muscle weakness, ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(88 citation statements)
references
References 18 publications
2
84
0
2
Order By: Relevance
“…The estimated median time to response was 9 days, and the median duration of response was 104 days. The most common adverse reactions were nausea, dyspnea, decreased appetite, headache, peripheral edema, vomiting, anemia, constipation, and diarrhea [30]. In clinical studies Denosumab was found to be well tolerated apart arthralgias and a risk of jaw osteonecrosis comparable to that of Zoledronate; no dose adjustment has been required in patients with renal impairment [21,22].…”
Section: Role Of Denosumab In Malignancy-associated Hypercalcemiamentioning
confidence: 99%
“…The estimated median time to response was 9 days, and the median duration of response was 104 days. The most common adverse reactions were nausea, dyspnea, decreased appetite, headache, peripheral edema, vomiting, anemia, constipation, and diarrhea [30]. In clinical studies Denosumab was found to be well tolerated apart arthralgias and a risk of jaw osteonecrosis comparable to that of Zoledronate; no dose adjustment has been required in patients with renal impairment [21,22].…”
Section: Role Of Denosumab In Malignancy-associated Hypercalcemiamentioning
confidence: 99%
“…Hu et al conducted a single arm study treating 33 patients having hypercalcemia of malignancy (corrected serum calcium .12.5 mg/dL) including both solid and hematologic tumors with denosumab (120 mg subcutaneously on days 1, 8, 15, 29, and every 4 weeks thereafter). 45 Following two injections of denosumab, 64% of patients achieved corrected calcium levels of #11.5 mg/dL and 36% reached calcium levels of #10.8 mg/dL. Over the course of the study, 70% of patients responded with a drop in calcium and 64% had a complete response.…”
mentioning
confidence: 92%
“…46 Seven patient records were analyzed representing a variety of diagnoses including multiple myeloma, non-Hodgkin's lymphoma, sarcoma, and cancer of unknown primary. In comparison with the trial reported above, 45 patients in this series received only a single dose of denosumab, either 60 mg (two patients) or 120 mg (five patients) administered within 2 weeks of admission. Six of the seven patients also received an intravenous bisphosphonate before the denosumab.…”
mentioning
confidence: 99%
“…Denosumab is a monoclonal antibody to receptor activator of nuclear factor kappa-B ligand (RANK-L) approved by the U.S. Food and Drug Administration (FDA) for use in the treatment of osteoporosis and recently, in the treatment of hypercalcemia of malignancy (2,3). To our knowledge, there are no reports of denosumab use for the treatment of severe hypercalcemia in individuals with ESRD on HD.…”
Section: Introductionmentioning
confidence: 99%
“…It received its initial FDA approval for the treatment of osteoporosis and skeletal related events in malignancies and, in 2014, also received an indication for use in hypercalcemia of malignancy refractory to bisphosphonate therapy (3). In a single-arm phase 2 trial of individuals with hypercalcemia of malignancy unresponsive to bisphosphonates, subsequent treatment with multiple doses of denosumab was able to lower calcium levels to ≤11.5 mg/dL in 70% of individuals; however, it should be noted that individuals on dialysis were excluded (2). In one of the earliest reported cases of denosumab use for hypercalcemia secondary to parathyroid carcinoma, refractory hypercalcemia was seen despite aggressive postoperative medical management with IVF, bisphosphonate, and cinacalcet (8).…”
mentioning
confidence: 99%